(untitled) (Revista Peruana de Investigación Educativa, 2014)
The incorporation of digital technologies into classroom practice confronts teachers with difficulties to carry out the idea that digital tool’s affordances are able to transform learning outcomes and teaching practice. This paper describes and presents data of a case study of one teacher’s process for incorporating technology into his geography class in a Mexican secondary school, his participation in a workshop whose purpose was to explore different digital tools and to develop ways of embedding these tools into the design of learning situations. The study aimed to analyze the teacher’s decision making process regarding the use of technology for teaching and explore his ideas about how to design learning activities and cope with institutional and technical constraints. This is a qualitative research; a microethnographic perspective, that allows to examine small social units and specific interaction, was used for data collection and analysis.